2023
DOI: 10.1111/jcms.13485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Green Advantage: Growth Regimes and Public Investment in Renewable Energy R&D

Abstract: Many consider research and development (R&D) a crucial pillar of decarbonization, yet few have investigated what actually drives investment. What drives public investment in renewable energy R&D in wealthy democracies? Using OECD data, this research note tests a number of hypotheses from the literature and finds that public investment in renewable energy R&D is most closely associated with growth regimes and their related characteristics. Furthermore, the ‘most invested’ are dynamic services export… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Most theories of comparative capitalism have revolved around this problem, from the French regulation school (Aglietta, 1979) and the social studies of accumulation (Kotz, McDonough, and Reich, 1994), to varieties of capitalism (Hall and Soskice, 2001) and growth model/growth regime theory (Baccaro and Pontusson, 2016;Hassel and Palier, 2020). Climate policy scholars, while rightly highlighting the "environmental silences" in this literature, have also argued that the insights from this field should be "repurposed" (Green, 2023, 330, 338) for the study of the political economy of decarbonisation (Baer, Campiglio, and Deyris, 2021;Copley, 2023;Cahen-Fourot, 2020;Nahm, 2022;Driscoll, 2023). Such repurposing will, however, require serious engagement with the pivotal role of macrofinancial institutions in determining which regimes offer a path to a just green transition, which do not, and why.…”
Section: Macrofinancial Regimesmentioning
confidence: 99%
“…Most theories of comparative capitalism have revolved around this problem, from the French regulation school (Aglietta, 1979) and the social studies of accumulation (Kotz, McDonough, and Reich, 1994), to varieties of capitalism (Hall and Soskice, 2001) and growth model/growth regime theory (Baccaro and Pontusson, 2016;Hassel and Palier, 2020). Climate policy scholars, while rightly highlighting the "environmental silences" in this literature, have also argued that the insights from this field should be "repurposed" (Green, 2023, 330, 338) for the study of the political economy of decarbonisation (Baer, Campiglio, and Deyris, 2021;Copley, 2023;Cahen-Fourot, 2020;Nahm, 2022;Driscoll, 2023). Such repurposing will, however, require serious engagement with the pivotal role of macrofinancial institutions in determining which regimes offer a path to a just green transition, which do not, and why.…”
Section: Macrofinancial Regimesmentioning
confidence: 99%
“…According to Bhattarai et al (2022), development and application of technology can be affected by direct policy investment. Driscoll (2023) found that investments in renewable energy R&D are most closely related to growth regimes and their associated characteristics. Green finance is also considered while evaluating the role of technology on renewable energy investments.…”
Section: Literature Reviewmentioning
confidence: 99%